El proceso de elegibilidad en Argentina: rituales y ambivalencias en el reconocimiento de los refugiados - Clavijo, Janneth Karime (2018)
Eligibility is a the central process in the construction of refugee policies and refugee status. These process refer to instances and mechanisms through which States evaluate asylum applications, which results in the recognition and granting of the Refugee Statute or rejection of such request. This paper examines the discourses about the eligibility process and the way these operate in the determination of refugee status in the Argentine context. The analysis is part of the studies that aim to visualize the dynamics through which populations are classified. Is proposed that within the categories of asylum seekers and refugees it is possible to observe a heterogeneity and ambivalence about the way in which subjects are perceived and classified.